The effectiveness of the treatment and prevention of canine in condition of veterinary clinics by LLC «Biocenter» in town Poltava - Коне, М. С.; Корчан, Л. М.; Забіяка, О. О. (Scientific Progress & Innovations, 2015)
Studied the age and pedigree sensitivity, seasonal occurrence and dynamics of display canine distemper in veterinary clinics by LLC «Biotcenter» in Poltava. We established that enzootic of canine distemper is often seen in the spring and summer are more likely to be infected dog breed of German shepherd. According to canine distemper we developed and proposed treatment regimen intestinal form which is much more effective than the conventional basic method. The importance of the use of chemotherapeutic agents at some stages of infection. We established that for the prevention of plague in dogs proved most effective vaccine «Nobivak DHPPI».